2013
DOI: 10.1073/pnas.1302028110
|View full text |Cite|
|
Sign up to set email alerts
|

mitoBK Ca is encoded by the Kcnma1 gene, and a splicing sequence defines its mitochondrial location

Abstract: The large-conductance Ca 2+ - and voltage-activated K + channel (BK Ca, MaxiK), which is encoded by the Kcnma1 gene, is generally expressed at the plasma membrane of excitable and nonexcitable cells. However, in adult cardiomyocytes, a BK Ca -like channel activity has been reported in the mitochondria but not at the plasma membrane. The putative opening of this channel with the BK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
290
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(302 citation statements)
references
References 20 publications
11
290
1
Order By: Relevance
“…In addition, Singh et al recently demonstrated that cardiomyocyte BKCa channels contain a novel C-terminal splice variant (termed DEC), which when expressed localizes the channel exclusively to cardiomyocyte mitochondria. 7 Importantly, there is no known expression of BKCa channels on the cardiomyocyte plasma membrane. Activation of plasma membrane K + currents could lead to altered action potential and arrhythmia, as seen with KATP modulating compounds.…”
Section: Expression In the Cardiovascular Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Singh et al recently demonstrated that cardiomyocyte BKCa channels contain a novel C-terminal splice variant (termed DEC), which when expressed localizes the channel exclusively to cardiomyocyte mitochondria. 7 Importantly, there is no known expression of BKCa channels on the cardiomyocyte plasma membrane. Activation of plasma membrane K + currents could lead to altered action potential and arrhythmia, as seen with KATP modulating compounds.…”
Section: Expression In the Cardiovascular Systemmentioning
confidence: 99%
“…40 In addition, Singh et al showed that mitochondria treated with NS1619 had increased resistance to Ca 2+ -induced MPTP opening. 7 Interestingly, both the BKCa activators, NS11021 and NS1619, elicit minor if any detectable depolarization of mitochondrial membrane potential when used at appropriate BKCa-activating concentrations. 15, 41 Therefore, charge-mediated limitations of Ca 2+ influx would likely be equally mild.…”
Section: Mechanism Of Mitochondrial Bkca-channel-mediated Cardioprotementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Ben-Tal et al (2009) modeled the multi-term inventory control problem conducive to optimize the expected cost that includes the costs of flows, transfer links, capacities, and middle-stage facility locations. Singh et al (2013) formulated a two-phase stochastic programming formulation for capacitated network design of an SC with flexible demands. Bayati et al (2013) proposed an optimal pricing and marketing planning where the primary objective function is to maximize the total profit.…”
Section: Scnd With Parameter Uncertaintymentioning
confidence: 99%
“…More recently, the Ca 2ϩ -activated large-conductance K ϩ (BKCa) channel has also been recognized as having potent cardioprotective properties. BKCa activation reduces myocardial infarction, promotes survival, and improves cardiac and vascular function following severe ischemic insults (3,7,9,12,31,32,34,36). In addition, BKCa channels may be more potently cardioprotective than mitoK ATP channels (17).…”
mentioning
confidence: 99%